1D Chiral Lead Bromide Perovskite with Superior Second‐Order Optical Nonlinearity, Photoluminescence, and High‐Temperature Reversible Phase Transition - Peng, Xin‐Lin; Han, Rui‐Rui; Tang, Yun‐Zhi; Tan, Yu‐Hui; Fan, Xiao‐Wei; Wang, Fang‐Xin; Zhang, Hao (Chemistry, an Asian journal, 2023)
Multifunctional materials are an attractive research area. Organic‐inorganic hybrid perovskites are widely used in the design of these materials due to their rich properties and flexible composition. It is easy to obtain more photoelectric properties by introducing chiral groups as ligands. In this work, we synthesized chiral one‐dimensional organic‐inorganic hybrid perovskites, namely (R/S‐3‐HP)PbBr3 (1R/1S) (3‐HP=3‐hydroxy‐piperidine). The enantiomer compounds undergo reversible phase transition at 349/336 K. Under the excitation light of 339 nm, 1R and 1S have a wide emission peak at 635 nm, showing orange light. In addition, the indirect bandgap is 3.29 eV and the SHG intensity is comparable to that of KDP. This work provides a way to design multifunctional chiral perovskite materials. Chiral 1D organic‐inorganic hybrid perovskites, namely, (R)‐ and (S)‐3‐HP PbBr3 (3‐HP=3‐hydroxy‐piperidine) wer synthesized. The enantiomer compounds undergo reversible phase transition at 349/336 K. Under UV light, they show orange light. In addition, the indirect band gap is 3.29 eV and the SHG intensity is comparable to that of KDP.